Falls in the Elderly: Determinants, Consequences and Prevention Approaches - Halik, Paulina; Jusiak , Justyna; Wydeheft , Lidia; Malon, Paulina; Lewiński, Jakub; Kędziora-Kornatowska , Kornelia (Quality in Sport, 2026)
Introduction: Falls among older adults are a major global public health problem and a leading cause of injury, disability and mortality in individuals aged 65 years and older. With population aging, the incidence and burden of falls are expected to increase. Falls result from complex interactions between intrinsic age-related changes and extrinsic environmental factors, making them a core geriatric syndrome requiring comprehensive management. Aim: This review aimed to summarize current evidence on the epidemiology, determinants, consequences, and prevention strategies for falls in older adults. Materials and Methods: A narrative review was conducted using PubMed, Scopus, and Web of Science databases. Peer-reviewed articles, meta-analyses, and clinical guidelines published between 2018 and 2025 were included. Results: Approximately one-third of community-dwelling adults aged ≥65 experience at least one fall annually, with higher rates among those aged ≥80 and residents of long-term care facilities. Major risk factors include advanced age, prior falls, gait and balance impairment, muscle weakness, frailty, multimorbidity, polypharmacy, visual and cognitive impairment, and environmental hazards. Falls often lead to fractures, head injuries, functional decline, psychological consequences such as fear of falling, and increased healthcare utilization. Discussion: The findings confirm the multifactorial nature of falls and the cumulative impact of modifiable and non-modifiable risk factors. Psychological consequences, particularly fear of falling, contribute to recurrent falls and progressive functional decline. Conclusions: Falls in older adults represent a complex geriatric syndrome with substantial clinical and socioeconomic consequences. Integrated, multifactorial prevention programs based on comprehensive geriatric assessment are essential to reduce fall risk, maintain independence, and mitigate healthcare system burden.